Talent Management in Healthcare Exploring How the World's Health Service Organisations Attract, Manage and Develop Talent - Turner, Paul (Springer International Publishing, 2018)
Providing a global perspective on the increasingly important concept of talent management in the health sector, this significant new text brings together evidence and research findings to suggest how healthcare organisations can attract and retain talent. The demand for healthcare in many countries often exceeds the supply of those who can provide it, and with case studies from Asia, the UK and the US, this book provides geographical insights into the extent of this global challenge. Topics discussed include employee engagement, employer branding, retention and succession planning. Talent Management in Healthcare offers readers a substantial guide and provides a sustainable talent strategy for organisations within the healthcare industry. An invaluable contribution to research on human resource development, this book will be of interest to academics and practitioners involved in organisational development, human resource management and healthcare management.